How to Enhance MSMEs Readiness? an Empirical Study in Semarang Municipality - Rusdarti, Rusdarti; Kistanti, Nurjanah Rahayu (JEJAK: Jurnal Ekonomi dan Kebijakan, 2018)
The absence of maximum readiness of the existing Micro Small Medium Enterprises or SMEs in Semarang City in facing the ASEAN Economic Community (AEC) requires an effort to improve the quality and competitiveness of SMEs. According to this problem, this research had several objectives to achieve, namely 1) evaluating the readiness of Semarang Municipality’s SMEs from various aspects in facing Asean Economic Community (AEC), 2) preparing the strategies to improve Semarang Municipality's SMEs business quality and capacity. This research uses descriptive and SWOT analyses. The research results indicate that SMEs in Semarang Municipality has been ready in facing AEC. The obstacles standing in the way of SMEs include poorly arranged administration, the absence of product standardization, and marketing. The strategies practicable to improve SMEs’ businesses in Semarang Municipality include improving and extending marketing network and organizing training, assistance and technology upgrade for SMEs to improve their product standard, value and quality.